Reduction of the self-dual Yang-Mills equations. I. The Poincaré group - Zhdanov, R.Z.; Lahno, V.I.; Fushchych, W.I. (Український математичний журнал, 1995)
For the vector potential of the Yang-Mills field, we give a complete description of ansatzes invariant under three-parameterP (1, 3) -inequivalent subgroups of the Poincaré group. By using these ansatzes, we reduce the self-dual Yang-Mills equations to a system of ordinary differential equations.